Les conditions d'exploitation et d'analyse des pratiques pour la formation des enseignants - Bulea, Ecaterina; Bronckart, Jean-Paul (Linguarum Arena, 2018)
Two different approaches currently dominate the teacher training field. One consists in the traditional transmission of knowledge and generally takes the form of conventional classroom teaching. The other, more recent and emerging from the domain of work sciences, consists in different methods for analysing teaching practices (interviews, peer instruction, self-confrontation, etc.) so that future teachers can be confronted with real-life situations and become aware of some of the characteristics of the profession they have chosen. The first part of this article examines the conditions and reasons for the emergence of practice analysis in teacher training, starting with the example of the recent evolution in the field of mother tongue didactics. The second part presents a critical assessment and balance of this evolution. On the one hand, it highlights the need for a deep change in the “logic” underlying innovative initiatives in the field; on the other hand, it formulates proposals to redefine teacher training objectives and methods by focussing on a close association between the classical methods of knowledge transmission and the more recent methods of teaching practice analysis. The third part analyses the characteristics of some of the methods used in teaching practice analysis, focussing on the nature of their “objects”, their intelligibility, and the role they play in raising trainees’ awareness about their own development. Finally, the last part of the article is devoted to trainees’ own verbal production during practice analysis, with a view to highlighting the discursive processes used by trainees to (re)construct the meaning of their activity, which in turn leads them to question the very conditions under which teaching practice analysis truly contributes to their personal and professional development.